An Optimal Segmentation Technique for Near-Infrared Forearm Subcutaneous Veins - C.M. Goh, Ramani Subramaniam, Sayed Ahmad Zikri B Sayed Aluwee, M.T. Chai, S.A. Ali Shah (International Journal of Advanced Science and Technology, 2020)
Peripheral difficult venous access (PDVA) is a problem in peripheral intravenous catheterization (PIVC) procedures that cause veins damage/injury to patients. Various methods of forearm’s Subcutaneous vein localization using Near-Infrared (NIR) imaging were proposed to improve the problem of PDVA but no vein segmentation technique of NIR image yet has been proposed. Veins are challenging to visualize in NIR image, and physiological factors such as hair and dark skin tone impede the detection of vein pixels in NIR forearm images. This paper determines the optimum filter for NIR forearm vein segmentation through analyses and comparative experiments of several vein filters